Analysis Of The Level Of Adolescent Knowledge About Sexual Violence On Adolescent Attitudes In Sexual Violence Prevention - Vika Rachmania Hidayah (Buana Gender: Jurnal Studi Gender dan Anak, 2023)
Teenagers who should be the future of the nation are now a scourge for the wider community. The problem of sexual violence, exploitation and prostitution is currently rife throughout Indonesia. Sexual violence cases in Tegal Regency were ranked number three highest in Central Java. The objectives of this study include: a). To find out the level of knowledge and attitudes of adolescents in Tegal Regency about sexual violence. b). To analyze the relationship between the level of knowledge and attitudes of adolescents about sexual violence in Tegal Regency. The research method used in this study is qualitative method. The results of research from 150 respondents who have been interviewed, show that adolescents still have low knowledge about sexual violence. The average of them does not know that they have become perpetrators or victims of sexual violence. Just knowing they don't, let alone realizing it to take action in responding to this. Knowledge of sexual violence, greatly influences the attitude of adolescents. The lack of knowledge of adolescents about sexual violence has led to the low attitude of adolescents in supporting the prevention of sexual violence, especially in Tegal Regency.